Sustainable Construction Practices in Nigeria: A Structural Equation Modeling Approach - Unegbu, Hyginus; Yawas, D.S.; Dan-asabe, B.; Alabi, A.A. (Journal of Sustainable Infrastructure, 2024)
This study investigates the determinants of sustainable construction practices in Nigeria, focusing on the roles of regulatory frameworks, financial incentives, organizational readiness, and awareness and knowledge among stakeholders. Utilizing a cross-sectional survey design, data were collected from 255 experts in the construction sector, consisting of architects, project managers and engineers. The analysis utilized Structural Equation Modeling (SEM) to explore the direct and indirect effects of these factors on the sustainable construction practices adoption. The findings reveal that awareness and knowledge have the most significant impact, highlighting the critical need for education and information dissemination in advancing sustainability. Additionally, robust regulatory frameworks and financial incentives were identified as crucial enablers, facilitating the implementation of sustainable practices by setting standards and reducing financial barriers. Organizational readiness, encompassing leadership support and resource availability, also emerged as a key determinant, mediating the effects of policies and incentives. The study concludes that a multifaceted approach involving strong policies, financial support, and enhanced organizational capacity is essential for promoting sustainable construction in Nigeria. These findings are valuable guide to policymakers, industry stakeholders, and educators in their efforts to foster an environmentally sustainable construction sector.